Lean on Me Against COVID-19: Dyadic Coping as a Mediator Between Emotional Distress and Relationship Quality - Ramos, Sara Maria de Moura (2021)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação